Fluctuations in Neuroticism Due to COVID-19: A Case Study of Four Timelines: [Fluktuasi Neuroticism Akibat COVID-19: Studi Kasus Empat Lini Masa] - Natalya, Lina; Sin, Gabrielle Sinata; McCroskey, Lynda (ANIMA Indonesian Psychological Journal, 2024)
Neuroticism is a part of the human personality which consists of several negative emotions. The level of neuroticism has a tendency to become unstable, when individuals are faced with a traumatic event, including when the COVID-19 pandemic hit. In order to obtain a more in-depth picture of the fluctuation level of neuroticism (negative emotions), this study measured neuroticism score utilizing the Big Five Inventory-2 (BFI-2) on 1,911 subjects in the age range of 18-25 years. This measurement was carried out longitudinally, with details of measurements on four timelines. All data collection process was carried out by accidental random sampling. This study proves that there is fluctuating trend in each aspect of neuroticism. The aspects of anxiety and neuroticism have a decreasing trend, the aspect of depression has an increasing trend, and the aspect of emotional volatility has a stable trend. The occurrence of these fluctuations proves that COVID-19 affects life aspects of most individuals. Neuroticism merupakan bagian dari kepribadian manusia yang terdiri atas sejumlah emosi negatif. Tingkat neuroticism memiliki kecenderungan untuk berubah menjadi tidak stabil, ketika individu dihadapkan pada sebuah peristiwa traumatis, tidak terkecuali ketika pandemi COVID-19. Guna memperoleh gambaran yang lebih mendalam mengenai tingkat fluktuasi neuroticism (emosi negatif) tersebut, studi ini mengukur skor neuroticism menggunakan Big Five Inventory-2 (BFI-2) pada 1.911 subjek pada rentang usia 18-25 tahun. Pengukuran ini dilakukan secara longitudinal, dengan rincian pengukuran pada empat lini masa. Seluruh proses pengumpulan data dilakukan dengan accidental random sampling. Studi ini membuktikan bahwa terdapat tren fluktuasi pada tiap aspek neuroticism. Aspek anxiety dan neuroticism memiliki tren menurun, aspek depression memiliki tren meningkat, dan aspek emotional volatility memiliki tren stabil. Terjadinya fluktuasi ini membuktikan bahwa COVID-19 memengaruhi aspek kehidupan sebagian besar individu.